Does amaranth have the agronomic potential to be a global phenomenon like quinoa - Espitia Rangel, Eduardo; Hernández, Luisa Fernanda Sesma; Ramos, Miriam Gabriela Valverde; Molina, Lucila González; López, Diana Escobedo; Aguilar Delgado, Miriam Jazmín (Revista Mexicana de Ciencias Agrícolas, 2021)
Amaranth and quinoa belong to the family Amaranthaceae characterized by having species that grow in adverse conditions, in addition to presenting high contents of proteins, unsaturated fatty acids and vitamins, as well as functional properties, which could be an excellent option to face the great problems that afflict the world. Due to these characteristics, quinoa has become a worldwide phenomenon and is already grown in more than 100 countries. The study was proposed in order to determine if amaranth has the agronomic potential to increase the cultivated area as happened with quinoa. An experiment was established with three varieties of quinoa and three varieties of amaranth in three environments of the Highs Valleys of Mexico, under a randomized complete block design with an arrangement of treatments in split plots. Agronomic variables, as well as yield, were evaluated. The results found showed that amaranth surpassed quinoa in inflorescence length, inflorescence width, stem diameter, hectoliter weight and yield, while quinoa presented higher values for seed diameter and weight of one thousand seeds. The Tlahuicole and L-145 amaranth genotypes observed the best performance, followed by the Suyana variety of quinoa. Amaranth has characteristics to be a worldwide phenomenon, as has happened with quinoa.
Keywords: Amaranthus spp.; Chenopodium quinoa; varieties; yield